Hubungan antara Pengetahuan tentang Hukum Perawatan Ortodonti dalam Pandangan Islam terhadap Persepsi Tenaga Pendidik Pondok Pesantren Modern terkait Perawatan Ortodonti - Nafsih, Thoharoh Laili; Handayani, Fani Tuti; Nurlaela, Nurlaela; Wardhianna, Sotyania; Purnama, Ryana Budi (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Background: Malocclusion is a condition of occlusion deviation which is still the third-highest dental and oral health problem in Indonesia. The high prevalence of malocclusion in Indonesia has not been followed by public awareness to perform orthodontic treatment. The awareness and behavior of people to get treatment can be influenced by knowledge and perceptions. Objective: to analyze the relationship between knowledge about the laws of orthodontic treatment according to Islamic perspective and the perceptions of modern Islamic boarding school teachers regarding orthodontic treatment Methods: This study used an analytic observational method with a cross-sectional approach. The research was conducted at Zam-Zam Muhammadiyah Cilongok Islamic Boarding School. Sample selection was carried out using the simple random sampling technique with the inclusion and exclusion criteria. Knowledge and perceptions are measured using the questionnaire. A total of 78 teachers participated in this study and 50 respondents who met the criteria were obtained. Data analysis was performed by descriptive and inferential analysis using the Chi-square test. Results: The data obtained shows that the knowledge of teachers is dominated by knowledge in the good category (52%) and there are no respondents in the bad category of knowledge. Perceptions of teachers are dominated by moderate perceptions (68%) and there are no respondents in the bad category of perceptions. The results of the Chi-square test obtained a value of p = 0.000 (p